Factors Of EFL Students’ language Anxiety In English Learning - Arifin, Advalina August Anggraeni; Malihah, Noor; Nabella, Angelia Cipta Riska (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Extraordinary anxiety can impede the abilities and accomplishment of mastering English. Hence the right technique is expected to conquer this issue. This study aimed to recognize the factors of language anxiety that foreign language students encounter. In this paper, the types and the reasons for language anxiety among EFL students will be talked about. This research applied Systemic Literature Review (SLR), is a technique for getting information from previous research on the subject at hand. It used 20 articles about students’ language anxiety. After analyzing these articles, there are 19 articles utilizing the SLR technique, it demonstrates the way that few elements of language anxiety can be recognized into internal variables and external factors. These two aspects cannot be understated and may be linked. Despite this, it is not unheard of for the same things to cause different levels of anxiety. Language anxiety can be divided into internal and external factors, such as background, personality, English tests, inability to deliver ideas, L1 accent, mispronunciation, lack of English grammatical structure and vocabulary, inadequate preparation, lack of practice, and anxiety about making mistakes.